SIGI TENTANG PENGGUNAAN BAHAN AJAR MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 19 SURABAYA - VINAYA SUCI WIHARANY (Jurnal Pendidikan Akuntansi (JPAK), 2013)
The research aimed at teaching material used to know and the teaching materials and using the appropriate teaching materials used in economic subjects matter accounting class XI Social in high school of 19 Surabaya. The type of research is research descriptive. To the subject of study was the teacher accounting and object research is teaching materials used in economic subjects matter accounting class XI Social in high school of 19 Surabaya and to instrument used is the an interview and poll examine the teaching materials, as for technical data using interviews, documentation and poll examine the teaching materials. The research result that the teaching material used on the subjects of accounting is Accounting worksheets “Kharisma”. The reason to use these worksheets due to affordable price for students. As for the results of the feasibility, Accounting worksheets “Kharisma” used in economic subjects matter accounting XI Social in high school of 19 Surabaya is feasible. Keywords: Survey, Teaching Materials, Subjects Accounting